Preparation of UHTCMCs by hybrid processes coupling Polymer Infiltration and Pyrolysis with Hot Pressing and vice versa. Issue 5 (May 2022) - Servadei, Francesca; Zoli, Luca; Galizia, Pietro; Melandri, Cesare; Sciti, Diletta
Abstract: Carbon fibre reinforced ultra-high temperature ceramic (UHTC) matrix composites were fabricated coupling water-based powder slurry infiltration, Polymer Infiltration and Pyrolysis (PIP) and Hot Pressing (HP) techniques. This study aims to identify the best sequence of consolidation techniques to better integrate the carbon fibre cloths into an ultra-refractory sintered ceramic matrix of ZrB2 -SiC. Infiltrated preforms with UHTC powder slurry were densified via: a) a pre-sintering step by HP followed by two PIP cycles with polycarbosilane, and vice versa, b) two PIP cycles followed by a cycle of HP. Flexural strengths at room temperature and at 1500 °C (167 MPa and 592 MPa, respectively) were found to be significantly higher for composites obtained by the second route, suggesting that sintering of polymer-derived SiC during HP improves the structural properties of Cf /ZrB2 -SiC composites. This work presents an effective method for UHTCMC manufacturing in a shorter time than traditional PIP process.